Skrining Kesehatan Melalui Pemeriksaan Asam Urat di Kompleks Aditarina Kota Makassar - Mutmainnah Abbas; Rosdiana Mus; Thaslifa Thaslifa; Yanti Sunaidi; Fitriana Fitriana (Pusat Riset dan Inovasi Nasional, 2023)
Degenerative disease is one of the classes of diseases whose incidence is related to the degeneration process in old age whose development is directly related to time and age. This usually affects the joints, namely gout. Uric acid is the final metabolic product of purine, which is a component of nucleic acid found in the nucleus of body cells. Increased uric acid levels in the blood are not only caused by food consumed but there are several other factors, namely age, gender, body mass index, and genetics. In addition, in the elderly there is a decrease in the function of vital organs such as the liver and kidneys which can cause an increase in uric acid levels in the blood. The purpose of this study is health screening through uric acid examination. The method used was descriptive by involving 27 respondents who were willing to become subjects. The results showed that there were 10 respondents with increased uric acid examination results while 17 subjects showed normal uric acid examination results.